2010
DOI: 10.1080/00480169.2010.68868
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent avian malaria and avipox virus infection in translocated South Island saddlebacks (Philesturnus carunculatus carunculatus)

Abstract: Although the Plasmodium spp. identified is thought to be endemic to saddlebacks in New Zealand, the affected birds were likely to be immunocompromised by concurrent APV infection or through lack of genetic diversity. Both the introduced mosquito Culex quinquefasicatus and the native mosquito Culex pervigilans are likely vectors for both these diseases, and the provision of water supplies less favourable to mosquito-breeding is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 16 publications
1
40
0
Order By: Relevance
“…haemoparasites, and avipox virus (Hale & Briskie 2009;Alley et al 2010). In mammals, experiments have shown that TLR2 forms heterodimers with TLR1/TLR6/ TLR10 to recognize di-and tri-acylated lipoproteins/peptides (Buwitt-Beckmann et al 2006).…”
Section: Inferring Contemporary Selection On Motuara Island (Tlrs)mentioning
confidence: 99%
See 2 more Smart Citations
“…haemoparasites, and avipox virus (Hale & Briskie 2009;Alley et al 2010). In mammals, experiments have shown that TLR2 forms heterodimers with TLR1/TLR6/ TLR10 to recognize di-and tri-acylated lipoproteins/peptides (Buwitt-Beckmann et al 2006).…”
Section: Inferring Contemporary Selection On Motuara Island (Tlrs)mentioning
confidence: 99%
“…While anthropogenic practices are common causative agents for population bottlenecks of threatened species, natural processes such as disease outbreaks may induce further population declines (Hale & Briskie 2009;Alley et al 2010;Ujvari & Belov 2011). In the case of disease, effects on genetic diversity at functional loci may differ from effects on neutral genetic diversity due to selective forces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2A). P. elongatum lineage GRW06 has been isolated from both North and South Island saddlebacks (Philesturnus carunculatus rufusater and P. carunculatus carunculatus, respectively; Alley et al 2010). Additional sequence is therefore needed to determine whether RBG2 also corresponds to this parasite lineage.…”
Section: Sequence Analysis Ofmentioning
confidence: 99%
“…Several factors probably interact to determine the severity and pathogenicity of Plasmodium infections, including parasite species and lineage, co-infection with multiple malarial parasites or concomitant infection with other pathogens, and host species, sex, or age (Weatherhead & Bennett 1992;Valkiū nas 2005;Marzal et al 2008;Palinauskas et al 2008;Alley et al 2010). The ecological and life history context of infection may also contribute to both the severity of primary infection and recrudescence of chronic infections by influencing host condition and stress-mediated responses during periods of poor food availability or unfavourable environmental conditions, or as the result of trade-offs between resources allocated to immune system function and energetically costly behaviours such as breeding and migration (Applegate 1970;Sheldon & Verhulst 1996;Møller 1997;Nordling et al 1998;Merino et al 2000;Garvin et al 2006;French et al 2009;Knowles et al 2010).…”
Section: Introductionmentioning
confidence: 99%